Economics of labour force participation - Bowen, William G.; Finegan, T. Aldrich (New Jersey, 1969)
The authors of any study as quantitative as this one are apt to be regarded with suspicion by people who know that "looking at the numbers" for too long a time can lead to interpretations which fail to come close to the whole truth. Perhaps we can allay this suspicion at least in part by the very act of recognizing the grounds for it-and by citing one (nonsubstantive) case in point. According to our records, we have been working on this study for six years; the number six, however, seems a hopelessly. inadequate description of the longevity of the project! The enterprise started innocently enough when one of us showed the other a scatter gram relating labor force participation rates for married women to unem ployment rates in large metropolitan areas just at a time the other was thinking more generally about the relevance of labor force data for fiscal policy. It quickly took on a life of its own, resisted vigorously all efforts to curb its expansionist tendencies and its appetite for computer time, and finally ended only when the authors were faced with a now-or-never ultimatum posed by the approach on the horizon of a huge wave of new data (the 1970 Census).
Keywords: Labour and labouring classes